PENERAPAN SISTEM MANAJEMEN MUTU UNTUK MENDUKUNG PEMBELAJARAN INOVATIF DI SEKOLAH DASAR - Tri Mulyani, Endang; Siti Lestari Dwi Wahyuningsih; Anam Sutopo; Sabar Narimo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The implementation of Quality Management Systems (QMS) plays a strategic role in improving the quality of education in primary schools, particularly in supporting the development of innovative learning. This study aims to analyze the application of QMS at SDN 03 Dayu Karanganyar and how its integration can foster learning innovation. A qualitative approach with a case study method was employed, involving observations, in-depth interviews, and documentation analysis. The findings indicate that the application of QMS helps create a more organized learning process and supports innovations such as the use of digital technology and project-based approaches. However, challenges such as limited facilities, gaps in teachers' competencies in utilizing technology, and a lack of systematic evaluation remain obstacles. To optimize the integration of QMS with innovative learning, intensive teacher training, provision of supporting facilities, and strengthening data-driven quality policies are required. With these strategic measures, QMS can serve as an effective framework for establishing high-quality and adaptive primary education to address the challenges of the digital era.